Examining the role of family sociology, managerial support, and working conditions in determining teacher performance in Indonesia: the mediating role of motivation and professional development - Ulfah, Maria; Syahrudin, Husni; Thoharudin, Munawar; Wardani, Sandra Fitria; Kholifah, Nur (Frontiers in Education, 2024)
In developing countries like Indonesia, responsible agencies have yet to consider in-depth factors in building better teacher performance in secondary education. Contemporary educational research has explored the relationship between motivation and professional development on teacher performance. However, there needs to be more understanding of this relationship with family sociological conditions, levels of managerial support, and different working conditions. This research examines how motivation and professional development can determine teacher performance by involving these three conditions. This research involved 474 secondary education teachers voluntarily and with specific criteria profiles tailored to their needs. Data collection was assisted using a closed questionnaire with a four-point Likert scale, tested for validity and reliability. Structural Equation Modeling was used to analyze data through path analysis and bootstrap methods. The findings prove the importance of motivation and professional development supported by family sociological conditions, managerial support, and proportional workload in determining teacher performance. These results shed light on secondary education providers in strengthening professional development and simultaneously strengthening teacher motivation which has so far often been overlooked. The strategy used is to provide support in the managerial aspect to create work comfort and a proportional workload to make it easier for teachers to carry out technical development. Lastly, support and positive relationships from the family contribute to strengthening the teacher's mentality which leads